The Other (Muscarinic) Acetylcholine Receptors in Sympathetic Ganglia: Actions and Mechanisms - Brown, D.A. (Нейрофизиология, 2013)
Acetylcholine released from preganglionic sympathetic fibers can activate two types of acetylcholine receptors in sympathetic neurons, nicotinic and muscarinic. The former are ligand-gated ion channels responsible for direct synaptic transmission; the latter are G protein-coupled receptorsthat mediate variousindirect modulatory effects. Most mammalian sympathetic neurons express three muscarinic receptor subtypes, M1, M2, and M4; some also express M3 receptors. Activation of M1 receptors stimulates the G protein Gq and causes a slow postsynaptic depolarization and an increase in the excitability, ultimately leading to an asynchronous action potential discharge, which can “break through” the nicotinic ganglion block. This is largely mediated by closure of voltage-gated K+ channels (the M channels) composed of Kv7.2 and Kv7.3 subunits and results from hydrolysis and depletion of membrane phosphatidylinositol-4,5-bisphosphate. Activation of M2 receptors hyperpolarizes and inhibits the postsynaptic neuron by opening G protein-gated inwardly-rectifying Kir K+ channels via the G protein Gi. M4 receptors inhibit N-type (CaV(2)) calcium channels via the G protein Go. In the postganglionic neuron somata, this enhances the excitability by reducing calcium-dependent potassium currents. Conversely, in postganglionic processes and axon terminals, CaV(2)-mediated inhibition reduces norepinephrine release and inhibits postganglionic transmission. Different muscarinic receptors may be anatomically segregated with their cognate G proteins and (in some cases) ion channels in signalling microdomains.